ARAB PRA-ISLAM, SISTEM POLITIK KEMASYARAKATAN DAN SISTEM KEPERCAYAAN DAN KEBUDAYAAN - H.M. Nasron HK; Anisa Yusilafita; Dentha Andriyanti Mawarni; Nurul Pangesty (Sekolah Tinggi Ilmu Syariah Nurul Qarnain Jember, 2023)
This paper aims to examine the socio-religious conditions of Arab community before it was touched by Islam. This is because the customs, norms or values held by the community can change from time to time. For example, the case of Arab society before it was touched by Islam known as jahiliyah. This term specifically identifies the lifestyle of the Arab community at that time which had many meanings such as beliefs and beliefs, customs and traditions and many other aspects. The series of events in the life of the Arab community behind the birth of Islam is very important to study because there is not a single event in the world that is separated from the socio-historical context with events before and after it. This paper uses a library research method where researchers will examine and analyze various literatures related to the condition of Arab society before the arrival of Islam with the aim of developing both theoretical and practical aspects. The results found that the Arab community at that time was that before being touched by Islam, the law of the jungle applied where the strong were in power, and those who were weak would be oppressed. A person gets praise and praise if he has power and will be abused and persecuted if he does not have power. The social and religious conditions of the Arab community are not very conducive when compared to the conditions after entering Islam. This means that with the arrival of Islam, the religious social conditions of the Arab community have changed and become more regular in accordance with Islamic religious norms. Thus Islam becomes very influential in changing the order of people's lives anywhere in the world